Balanced scorecard como sistemática de gestão em busca da melhoria contínua da qualidade organizacional - Boligon, Juliana Andréia Rüdell (2009)
The managerial decisions, inside of the context of global economy have been strongly marked by the imminent need of search and application of new techniques and tools of administrative administration. In that sense, Balanced Scorecard - BSC initially created as an evaluation system and organizational performance, and later used as a methodology of strategic administration, it is a systematic of administration capable to concentrate attentions, energies, motivations and resources of an organization in what it is essential, and what is essential is its success in the creation of value, through the defined strategies. In that way, this work intends to analyze how BSC, as systematic of administration, can serves as tool for support the unfolding of the organizational strategies and to contributes for the continuous improvement of the organizational quality. For the collection of the information we used the simple observation and a pre-structured interview, applied to the management of the organization in study. As main result we obtained the knowledge of which main benefits gained with BSC, as well as the main critical points. Considering the contribution of such information, it was proposed a methodology for implementing the BSC in the organization, providing a continuous improvement in the operational processes and, mainly, in the managerial processes, for the fact of that type of information is absent in this administration team. We proposed to implant the BSC, through the execution of apprenticeships, which are in number of three, and all are subdivided in phases. Therefore, the justification, to understand the continuous improvement of the quality of organizational processes, linked to the BSC, is the ability to align strategy, processes and people in the organization to reach a common goal, which is the key to achieve success in implementing the strategy.